Specialty choice among final-year medical students and house officers in Nigeria: implications for anaesthesia practice – a cross-sectional study - Thankgod Chukwunnonso Okonkwo; Gbolahan Deji Olatunji; Victor Mayowa Adeleye; Mukaila Oyegbade Akinwale (BMJ Open)
Objectives Nigeria’s doctor shortage is worsening with mass exodus and imbalanced specialty distribution. Anaesthesia faces particularly critical shortages. Medical graduate specialty choices have a vital impact on the workforce and are essential for healthcare planning. This study aimed to identify the current specialty preferences of final-year medical students and house officers in Nigeria, factors that affect such choices, and their implications for anaesthesia practice.Design We conducted a cross-sectional study among final-year medical students and house officers in Nigeria using a self-administered, semistructured electronic questionnaire. The survey question was divided into four sections: sociodemographic data, specialty preferences, factors considered in choosing a specialty, perception of anaesthesia posting and anaesthesia as a specialty.Setting The survey was delivered via a Google Form that had been active for 4.5 months.Participants A total of 760 valid responses were received from final-year medical students and house officers in Nigeria. The majority (63.82%) of the participants were final-year medical students.Results Surgery (26.58%), internal medicine (14.47%) and obstetrics and gynaecology (14.34%) were the top-ranking specialty choices. Only 3.55% (eighth in ranking) intended to specialise in anaesthesia. There was a positive correlation between respondents’ specialty choice and the specialty of their doctor role model. Passion/interest, flexibility, potential future income and job prospects were essential in choosing a specialty. Most decisions were made during clinical rotations (63.95%), and only 35.26% had career guidance. Many enjoyed their anaesthesia posting, but over half felt the exposure was inadequate.Conclusions Too few medical graduates in Nigeria prefer anaesthesia as a specialty, and there is an urgent need to increase interest. A lack of career counselling, anaesthetist mentors and satisfactory clinical rotations are factors that can be improved for better recruitment into anaesthesia.